2019
DOI: 10.3390/cells8040331
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Lysate Inhibits NF-κB Activation and Induces Proliferation and an Alert State in Quiescent Human Umbilical Vein Endothelial Cells Retaining Their Differentiation Capability

Abstract: : Injured blood vessel repair and blood circulation re-establishment are crucial events for tissue repair. We investigated in primary cultures of human umbilical vein endothelial cells (HUVEC), the effects of platelet lysate (PL), a cocktail of factors released by activated platelets following blood vessel disruption and involved in the wound-healing process triggering. PL exerted a protective effect on HUVEC in an inflammatory milieu by inhibiting IL-1α-activated NF-κB pathway and by inducing the secretion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(68 reference statements)
1
8
0
1
Order By: Relevance
“…Thus, the presence of the von Willebrand factor after 7 days of culturing indicated that the co-culture containing keratinocytes and NF membranes did not interfere with the endothelial cell maturation process. These results are in agreement with those of other authors who indicated that PL acts to enhance endothelial cell proliferation without affecting their differentiation capacity [ 51 ].…”
Section: Discussionsupporting
confidence: 94%
“…Thus, the presence of the von Willebrand factor after 7 days of culturing indicated that the co-culture containing keratinocytes and NF membranes did not interfere with the endothelial cell maturation process. These results are in agreement with those of other authors who indicated that PL acts to enhance endothelial cell proliferation without affecting their differentiation capacity [ 51 ].…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, VEGF is playing a significant role both in osteoblasts differentiation and in the angiogenesis induction [ 29 , 47 , 48 ]. Moreover, in a recent publication, we reported that PL has a direct effect on endothelial cells by inducing their proliferation while maintaining their differentiation potential [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We reported that the platelet factors promoted the activation of the cell proliferation machinery and the cell-cycle re-entry of several types of cells, including chondrocytes and chondroprogenitors [ 18 , 19 , 20 ], human umbilical vein endothelial cells [ 21 , 22 ], bone marrow and umbilical cord mesenchymal stromal cells (MSCs) [ 21 , 23 ], adipose tissue cells [ 21 , 23 , 24 ], and amniotic fluid cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the released factors were evaluated for both our composite scaffold and PRP releasate (PRPr) in different cell types (endothelial, mesenchymal stromal cells, macrophages, fibroblasts, and keratinocytes) since all of them have key roles during different stages of wound healing (Gurtner et al, 2008;Eming et al, 2014). There is vast literature suggesting that PRP supports endothelial cell proliferation and induces angiogenesis/vascularization both in vitro and in vivo (Kakudo et al, 2014;Anitua et al, 2015;Notodihardjo et al, 2015;Etulain et al, 2018;Romaldini et al, 2019;Samberg et al, 2019). Our work corroborates those findings, but, importantly, shows that this activity is maintained within a biomaterial scaffold with proven regenerative potential.…”
Section: Discussionmentioning
confidence: 99%